Process for the preparation of a degradable cast film

CN122978563APending Publication Date: 2026-10-27FUJIAN JINGCHUANG INNOVATION MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611257792.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,由于碳酸钙为亲水性无机化合物,表面含有大量羟基结构,与有机高聚物的亲和性差,易形成聚集体,在高聚物内部分散不均匀,从而造成复合材料间界面缺陷,直接影响材料的加工性能和力学性能

Benefits of technology

本发明中碳酸钙占总质量65%左右,为高填充体系,将带来同等规格的薄膜物理性能提升20%;且由于碳酸钙的密度大于树脂,同等规格(面积)的薄膜重量更重,而薄膜产品按重量批量售卖,单位重量的产品可获取更高的销售收入。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978563A_ABST
    Figure CN122978563A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of cast film, and particularly relates to a preparation process of degradable cast film; the preparation process comprises the following steps: weighing polyethylene plastic, modified calcium carbonate, maleic anhydride grafted polyethylene compatilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula proportion, and uniformly mixing; the modified calcium carbonate is obtained by mixing dry calcium carbonate powder and long-chain alkyl quaternary ammonium salt-polyolefin block modifier; the mixed material is sent into a first-stage extruder for melt plasticization; the plasticized melt is sent into a vacuum degassing device for on-line wet extraction and bubble removal treatment; the degassed melt is sent into a second-stage extruder for secondary extrusion plasticization; the secondary plasticized melt is cast into a film through a T-shaped die head, and is wound after cooling and setting; the application realizes high filling of calcium carbonate, and significantly improves the mechanical properties and economic value of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cast film technology, specifically a process for preparing a biodegradable cast film. Background Technology

[0002] Cast film is a non-stretched, non-oriented flat extrusion film produced by melt casting and rapid cooling. It features high production speed, high output, and excellent film transparency and thickness uniformity, and is widely used in hygiene products, medical protective equipment, food packaging, and other fields. Currently, commonly used cast films use polyethylene (PE) and polypropylene (PP) as the main raw materials. Their molecular structure is stable and difficult to degrade in the natural environment. The large-scale disposal of disposable products causes serious "white pollution."

[0003] To reduce the cost of plastic films and improve their degradation performance, calcium carbonate is currently used as an inorganic filler for resins such as polyethylene in existing technologies. Calcium carbonate is the most widely used inorganic filler in polymer composites, with advantages such as wide availability, low price, and non-toxicity. However, because calcium carbonate is a hydrophilic inorganic compound with a large number of hydroxyl groups on its surface, it has poor affinity with organic polymers and easily forms aggregates. This uneven dispersion within the polymer leads to interfacial defects in the composite material, directly affecting its processing and mechanical properties. Summary of the Invention

[0004] To overcome the shortcomings of existing technologies and solve at least one of the technical problems mentioned in the background art, this invention designs and synthesizes a novel long-chain alkyl quaternary ammonium salt-polyolefin block bifunctional modifier as a modifier for calcium carbonate, fundamentally resolving the multiple contradictions of thermal stability, compatibility, and biodegradability. Based on this, combined with an integrated continuous casting process, high calcium carbonate filling is achieved, significantly improving the mechanical properties and economic value of the film.

[0005] The technical solution adopted by this invention to solve its technical problem is: a preparation process of a biodegradable cast film according to this invention, comprising the following steps: S1. Weigh out polyethylene plastic, modified calcium carbonate, maleic anhydride grafted polyethylene compatibilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula ratio, and mix them evenly. The modified calcium carbonate is obtained by mixing dried calcium carbonate powder with a long-chain alkyl quaternary ammonium salt-polyolefin block modifier. S2. The mixture is fed into the first-stage extruder for melt plasticization; S3. The plasticized melt is sent to a vacuum degassing device for online dehumidification and degassing treatment. S4. The degassed melt is fed into a second-stage extruder for secondary extrusion plasticization. S5. The melt after secondary plasticization is cast into a film through a T-die, cooled and shaped, and then wound up.

[0006] Preferably, the amount of long-chain alkyl quaternary ammonium salt-polyolefin block modifier added accounts for 2%-5% of the mass of calcium carbonate.

[0007] Preferably, the preparation of the long-chain alkyl quaternary ammonium salt-polyolefin block modifier includes: A long-chain alkyl quaternary ammonium salt-polyolefin block modifier is obtained by reacting carboxyl-terminated polyolefin, hydroxyethyl dimethyl hexadecyl quaternary ammonium salt, and 0.5%–2% of the total mass of the reactants with p-toluenesulfonic acid catalyst under toluene reflux for 8–12 hours.

[0008] Preferably, the molar ratio of carboxyl-terminated polyolefin to hydroxyethyl dimethyl hexadecyl quaternary ammonium salt is 1:2 to 1:2.5.

[0009] Preferably, the preparation of carboxyl-terminated polyolefins includes: Hydroxyl-terminated polyolefins are mixed with excess acid anhydride and reacted at 100-130°C under nitrogen protection for 4-8 hours to obtain carboxyl-terminated polyolefins.

[0010] Preferably, the molar ratio of hydroxyl-terminated polyolefin to acid anhydride is 1:1.2-1:2.

[0011] Preferably, by weight, the composition includes 100 parts polyethylene plastic, 185-195 parts modified calcium carbonate, 3-8 parts maleic anhydride grafted polyethylene compatibilizer, 0.5-2 parts antioxidant 168, 2-5 parts polyethylene wax dispersant, 1-3 parts stearic acid lubricant, and 3-6 parts polyolefin elastomer toughening agent.

[0012] Preferably, the modified calcium carbonate has a mesh size of 100-300.

[0013] Preferably, the extrusion temperature in S2 is 160-200℃; and the extrusion temperature in S4 is 170-210℃.

[0014] Preferably, the vacuum degree in S3 is -0.06 to 0.095 MPa, and the degassing time is 5 to 15 minutes.

[0015] The beneficial effects of this invention are as follows: In this invention, calcium carbonate accounts for about 65% of the total mass, making it a high-filling system that will improve the physical properties of films of the same specifications by 20%. Furthermore, since calcium carbonate has a higher density than resin, films of the same specifications (area) are heavier. Since film products are sold in batches by weight, higher sales revenue can be obtained per unit weight of product.

[0016] This invention relates to a long-chain alkyl quaternary ammonium salt-polyolefin block modifier obtained by reacting a carboxyl-terminated polyolefin with hydroxyethyl dimethyl hexadecyl quaternary ammonium salt. The long-chain alkyl quaternary ammonium cations can form strong ionic bonds with the anionic sites on the surface of calcium carbonate, strongly anchoring them to the calcium carbonate particles and ensuring robust interfacial bonding and excellent dispersibility. The quaternary ammonium salt has an aliphatic structure and can be degraded by microorganisms in nature, with degradation products being long-chain fatty acids and amines, which are non-toxic, harmless, and environmentally friendly.

[0017] Polyolefin blocks have similar chemical structures to the matrix resin, and according to the principle of "like dissolves like," they have a natural affinity. Polyolefin blocks can embed themselves into the molecular chain network of the polyolefin matrix, fundamentally eliminating the polarity difference between the modifier and the matrix.

[0018] Ester bonds are introduced as linking arms between quaternary ammonium salts and polyolefin blocks. These ester bonds can be broken under hydrolytic or enzymatic conditions, producing long-chain fatty acid and polyolefin oligomer fragments, which are environmentally acceptable small molecules that can be further utilized by microorganisms without interfering with the degradation pathway of the main resin. Attached Figure Description

[0019] Figure 1 This is a product image of the cast film prepared in Example 3 of the present invention. Detailed Implementation

[0020] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below in conjunction with specific embodiments.

[0021] Example 1 The preparation process of modified calcium carbonate according to an embodiment of the present invention includes the following steps: S1. Preparation of carboxyl-terminated polyolefins: Hydroxyl-terminated polyolefins (such as hydroxyl-terminated polybutadiene with a number average molecular weight of 1000) and excess acid anhydride (such as maleic anhydride) are added to a reaction vessel at a molar ratio of 1:1.2 and reacted at 100°C under nitrogen protection for 4 hours to obtain carboxyl-terminated polyolefins.

[0022] S2, Quaternary ammonium salt esterification: Carboxyl-terminated polyolefin and hydroxyethyl dimethyl hexadecyl quaternary ammonium salt (alkyl carbon number 12) are added to a reaction vessel at a molar ratio of 1:2. P-toluenesulfonic acid catalyst (0.5% of the total mass of reactants) is added, and the reaction is carried out under toluene reflux for 8 hours. Water generated in the reaction is removed by separation to obtain long-chain alkyl quaternary ammonium salt-polyolefin block modifier.

[0023] S3. Calcium carbonate surface modification: The dried calcium carbonate powder is put into a high-speed mixer, and 2% of the mass of calcium carbonate long-chain alkyl quaternary ammonium salt-polyolefin block modifier is added. The mixture is mixed at high speed for 15 minutes at 80℃ and 800 r / min to fully coat the surface of the calcium carbonate particles with the modifier, thus obtaining modified calcium carbonate.

[0024] Example 2 The preparation process of modified calcium carbonate according to an embodiment of the present invention includes the following steps: S1. Preparation of carboxyl-terminated polyolefins: Hydroxyl-terminated polyolefins (such as hydroxyl-terminated polybutadiene with a number average molecular weight of 3000) and excess acid anhydride (such as maleic anhydride) are added to a reaction vessel at a molar ratio of 1:1.6 and reacted at 120°C under nitrogen protection for 6 hours to obtain carboxyl-terminated polyolefins.

[0025] S2, Quaternary ammonium salt esterification: Carboxyl-terminated polyolefin and hydroxyethyl dimethyl hexadecyl quaternary ammonium salt (alkyl carbon number 15) are added to a reaction vessel at a molar ratio of 1:2.3. The catalyst p-toluenesulfonic acid (1.25% of the total mass of the reactants) is added, and the reaction is carried out under toluene reflux for 10 hours. The water generated in the reaction is removed by water separation to obtain a long-chain alkyl quaternary ammonium salt-polyolefin block modifier.

[0026] S3. Calcium carbonate surface modification: The dried calcium carbonate powder is put into a high-speed mixer, and a long-chain alkyl quaternary ammonium salt-polyolefin block modifier accounting for 3% of the mass of calcium carbonate is added. The mixture is mixed at high speed for 22 minutes at 90℃ and 1000 r / min to fully coat the surface of the calcium carbonate particles with the modifier, thus obtaining modified calcium carbonate.

[0027] Example 3 The preparation process of modified calcium carbonate according to an embodiment of the present invention includes the following steps: S1. Preparation of carboxyl-terminated polyolefins: Hydroxyl-terminated polyolefins (such as hydroxyl-terminated polybutadiene with a number average molecular weight of 5000) and excess acid anhydride (such as maleic anhydride) are added to a reaction vessel at a molar ratio of 1:2 and reacted at 130°C under nitrogen protection for 8 hours to obtain carboxyl-terminated polyolefins.

[0028] S2, Quaternary ammonium salt esterification: Carboxyl-terminated polyolefin and hydroxyethyl dimethyl hexadecyl quaternary ammonium salt (18 alkyl carbons) are added to a reaction vessel at a molar ratio of 1:2.5. P-toluenesulfonic acid catalyst (2% of the total mass of the reactants) is added, and the reaction is carried out under toluene reflux for 12 hours. The water generated in the reaction is removed by water separation to obtain a long-chain alkyl quaternary ammonium salt-polyolefin block modifier.

[0029] S3. Calcium carbonate surface modification: The dried calcium carbonate powder is put into a high-speed mixer, and a long-chain alkyl quaternary ammonium salt-polyolefin block modifier accounting for 5% of the mass of calcium carbonate is added. The mixture is mixed at high speed for 30 minutes at 100℃ and 1200r / min to fully coat the surface of the calcium carbonate particles with the modifier, thus obtaining modified calcium carbonate.

[0030] Example 4 The preparation process of a biodegradable cast film according to an embodiment of the present invention includes the following steps: Step 1: Weigh out polyethylene plastic, modified calcium carbonate prepared in Example 1, maleic anhydride grafted polyethylene compatibilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula ratio, put them into a high-speed mixer, mix at 60°C for 15 minutes to obtain a uniform mixture.

[0031] The composition, by weight, includes 100 parts polyethylene plastic, 185 parts modified calcium carbonate (100 mesh), 3 parts maleic anhydride grafted polyethylene compatibilizer, 0.5 parts antioxidant 168, 2 parts polyethylene wax dispersant, 1 part stearic acid lubricant, and 3 parts polyolefin elastomer toughening agent.

[0032] Step 2: Single-stage extrusion plasticizing. The mixture is fed into the first-stage twin-screw extruder for melt plasticizing. The extrusion temperature is controlled at 160℃ and the screw speed is 100r / min.

[0033] Step 3: Online dehumidification and degassing. The plasticized melt is fed into a vacuum degassing device and subjected to online dehumidification and degassing under a vacuum of -0.06 MPa for 5 minutes to remove moisture and air bubbles entrained in the melt.

[0034] Step 4: Secondary extrusion plasticizing. The degassed melt is fed into a second-stage single-screw extruder for secondary extrusion plasticizing. The extrusion temperature is controlled at 170℃ to further enhance the mixing and plasticizing of the components.

[0035] Step 5: Casting film. The melt after secondary plasticization is extruded through a T-die and cast onto the surface of a cooling roller. After cooling, shaping, traction, and trimming, a cast film is obtained.

[0036] Step Six: Corona Treatment. The cast film is corona treated before winding to achieve a surface tension of 36 dynes or higher, which is beneficial for subsequent printing or lamination processes.

[0037] Example 5 The preparation process of a biodegradable cast film according to an embodiment of the present invention includes the following steps: Step 1: Weigh out polyethylene plastic, modified calcium carbonate prepared in Example 1, maleic anhydride grafted polyethylene compatibilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula ratio, put them into a high-speed mixer, mix at 70°C for 25 minutes to obtain a uniform mixture.

[0038] The composition, by weight, includes 100 parts polyethylene plastic, 190 parts modified calcium carbonate (200 mesh), 6 parts maleic anhydride grafted polyethylene compatibilizer, 1.25 parts antioxidant 168, 3 parts polyethylene wax dispersant, 2 parts stearic acid lubricant, and 5 parts polyolefin elastomer toughening agent.

[0039] Step 2: Single-stage extrusion plasticizing. The mixture is fed into the first-stage twin-screw extruder for melt plasticizing. The extrusion temperature is controlled at 180℃ and the screw speed is 200 r / min.

[0040] Step 3: Online dehumidification and degassing. The plasticized melt is sent to a vacuum degassing device for online dehumidification and degassing under a vacuum of -0.075MPa for 5-15 minutes to remove moisture and air bubbles entrained in the melt.

[0041] Step 4: Secondary extrusion plasticizing. The degassed melt is fed into a second-stage single-screw extruder for secondary extrusion plasticizing. The extrusion temperature is controlled at 180℃ to further enhance the mixing and plasticizing of the components.

[0042] Step 5: Casting film. The melt after secondary plasticization is extruded through a T-die and cast onto the surface of a cooling roller. After cooling, shaping, traction, and trimming, a cast film is obtained.

[0043] Step Six: Corona Treatment. The cast film is corona treated before winding to achieve a surface tension of 36 dynes or higher, which is beneficial for subsequent printing or lamination processes.

[0044] Example 6 The preparation process of a biodegradable cast film according to an embodiment of the present invention includes the following steps: Step 1: Weigh out polyethylene plastic, modified calcium carbonate prepared in Example 1, maleic anhydride grafted polyethylene compatibilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula ratio, put them into a high-speed mixer, mix at 80°C for 30 minutes to obtain a uniform mixture.

[0045] The composition, by weight, includes 100 parts polyethylene plastic, 195 parts modified calcium carbonate (300 mesh), 8 parts maleic anhydride grafted polyethylene compatibilizer, 2 parts antioxidant 168, 5 parts polyethylene wax dispersant, 3 parts stearic acid lubricant, and 6 parts polyolefin elastomer toughening agent.

[0046] Step 2: Single-stage extrusion plasticizing. The mixture is fed into the first-stage twin-screw extruder for melt plasticizing. The extrusion temperature is controlled at 160-200℃, and the screw speed is 100-300 r / min.

[0047] Step 3: Online dehumidification and degassing. The plasticized melt is sent to a vacuum degassing device for online dehumidification and degassing under a vacuum of -0.095MPa for 15 minutes to remove moisture and air bubbles entrained in the melt.

[0048] Step 4: Secondary extrusion plasticizing. The degassed melt is fed into a second-stage single-screw extruder for secondary extrusion plasticizing. The extrusion temperature is controlled at 210℃ to further enhance the mixing and plasticizing of the components.

[0049] Step 5: Casting film. The melt after secondary plasticization is extruded through a T-die and cast onto the surface of a cooling roller. After cooling, shaping, traction, and trimming, a cast film is obtained.

[0050] Step Six: Corona Treatment. The cast film is corona treated before winding to achieve a surface tension of 36 dynes or higher, which is beneficial for subsequent printing or lamination processes.

[0051] Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the modified calcium carbonate used is unmodified calcium carbonate, while the other steps are the same.

[0052] The performance of the cast films prepared by the methods in Examples 3-6 and Comparative Example 1 was tested; the tensile strength test standard was GB / T 1040.3-2006; the elongation at break test standard was GB / T 1040.3-2006; the test results are as follows: As can be seen from the table above, this invention achieves uniform dispersion and strong interfacial bonding of calcium carbonate in the polyolefin matrix through the strong ionic bond anchoring effect between long-chain alkyl quaternary ammonium cations and the calcium carbonate surface, as well as the natural affinity between the polyolefin blocks and the matrix resin. Even with a high filling level of approximately 65% ​​of the total mass of calcium carbonate, the film still maintains excellent mechanical properties, showing an improvement of approximately 20% compared to conventional products of the same specifications. The cast films obtained in Examples 4-6 of this invention have smooth surfaces, free of crystal points and white spots, indicating that the modified calcium carbonate is uniformly dispersed in the polyolefin matrix. The cast film obtained in Comparative Example 1 has a large number of agglomerated white spots and a rough surface, further demonstrating the poor dispersion of unmodified calcium carbonate in the polyolefin matrix.

[0053] Thermogravimetric analysis was performed on the modifiers prepared in Examples 1-3, and the results are as follows: The quaternary ammonium salt in the modifier of this invention has a thermal decomposition temperature above 200℃, and the polyolefin block exhibits excellent thermal stability. The 5% thermal weight loss temperatures of Examples 1-3 are 282℃, 285℃, and 288℃, respectively, far exceeding the processing temperature of cast film (160-200℃), demonstrating stable resistance to high-temperature processing environments without decomposition or release of volatile organic compounds. In contrast, the 5% thermal weight loss temperature of the PEG-bisimidazole ionic liquid is only 195℃, posing a risk of decomposition under high-temperature processing conditions for cast film.

[0054] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a biodegradable cast film, characterized in that: Includes the following steps: S1. Weigh out polyethylene plastic, modified calcium carbonate, maleic anhydride grafted polyethylene compatibilizer, antioxidant 168, polyethylene wax dispersant, stearic acid lubricant and polyolefin elastomer toughening agent according to the formula ratio, and mix them evenly. The modified calcium carbonate is obtained by mixing dried calcium carbonate powder with a long-chain alkyl quaternary ammonium salt-polyolefin block modifier. S2. The mixture is fed into the first-stage extruder for melt plasticization; S3. The plasticized melt is sent to a vacuum degassing device for online dehumidification and degassing treatment. S4. The degassed melt is fed into a second-stage extruder for secondary extrusion plasticization. S5. The melt after secondary plasticization is cast into a film through a T-die, cooled and shaped, and then wound up.

2. The preparation process of a biodegradable cast film according to claim 1, characterized in that: The amount of long-chain alkyl quaternary ammonium salt-polyolefin block modifier added is 2%-5% of the mass of calcium carbonate.

3. The preparation process of a biodegradable cast film according to claim 2, characterized in that: The preparation of long-chain alkyl quaternary ammonium salt-polyolefin block modifiers includes: A long-chain alkyl quaternary ammonium salt-polyolefin block modifier is obtained by reacting carboxyl-terminated polyolefin, hydroxyethyl dimethyl hexadecyl quaternary ammonium salt, and 0.5%-2% of the total mass of the reactants with p-toluenesulfonic acid catalyst under toluene reflux for 8-12 hours.

4. The preparation process of a biodegradable cast film according to claim 3, characterized in that: The molar ratio of carboxyl-terminated polyolefin to hydroxyethyl dimethyl hexadecyl quaternary ammonium salt is 1:2 to 1:2.

5.

5. The preparation process of a biodegradable cast film according to claim 4, characterized in that: The preparation of carboxyl-terminated polyolefins includes: Hydroxyl-terminated polyolefins are mixed with acid anhydrides and reacted at 100-130°C under nitrogen protection for 4-8 hours to obtain carboxyl-terminated polyolefins.

6. The preparation process of a biodegradable cast film according to claim 5, characterized in that: The molar ratio of hydroxyl-terminated polyolefin to acid anhydride is 1:1.2-1:

2.

7. The preparation process of a biodegradable cast film according to claim 6, characterized in that: In S1, the formula, by weight, consists of 100 parts polyethylene plastic, 185-195 parts modified calcium carbonate, 3-8 parts maleic anhydride grafted polyethylene compatibilizer, 0.5-2 parts antioxidant 168, 2-5 parts polyethylene wax dispersant, 1-3 parts stearic acid lubricant, and 3-6 parts polyolefin elastomer toughening agent.

8. The preparation process of a biodegradable cast film according to claim 7, characterized in that: The mesh size of modified calcium carbonate is 100-300 mesh.

9. The preparation process of a biodegradable cast film according to claim 8, characterized in that: The extrusion temperature in S2 is 160-200℃; the extrusion temperature in S4 is 170-210℃.

10. The preparation process of a biodegradable cast film according to claim 9, characterized in that: In S3, the vacuum level is -0.06 to 0.095 MPa, and the degassing time is 5 to 15 minutes.